Effects of Texas State Agency Integration on Mental Health Service Use Among Individuals with Co-occurring Cognitive Disabilities and Mental Health Conditions. - Stone, Elizabeth M.; Jopson, Andrew D.; Seewald, Nicholas J.; Stuart, Elizabeth A.; Wise, Elizabeth; McCourt, Alexander D.; German, Danielle; McGinty, Emma E. (Community Mental Health Journal, 2025)
This study uses Texas's 2017 integration of the state disability and mental health agencies as a case study, combining interviews with Texas agency and advocacy organization leaders to examine perceptions of agency integration and augmented synthetic control analyses of 2014–2020 Medical Expenditure Panel Survey to examine impacts on mental health service use among individuals with co-occurring cognitive disabilities (including intellectual and developmental disabilities) and mental health conditions. Interviewees described the intensive process of agency integration and identified primarily positive (e.g., decreased administrative burden) impacts of integration. Quantitative analyses indicated no effects of integration on receipt of mental health-related services among people with co-occurring conditions. While leaders identified some potentially beneficial impacts of state agency integration, the limited impact of integration beyond the agency suggests that interventions at multiple levels of the service system, including those targeting providers, are needed to better meet the mental health service needs for this population.